2016
DOI: 10.3389/fphys.2016.00156
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Hydrogen Sulfide in Inflammatory and Neoplastic Colonic Diseases

Abstract: Hydrogen sulfide (H2S) is a toxic gas that has been recognized as an important mediator of many physiological processes, such as neurodegeneration, regulation of inflammation, blood pressure, and metabolism. In the human colon, H2S is produced by both endogenous enzymes and sulfate-reducing bacteria (SRB). H2S is involved in the physiological and pathophysiological conditions of the colon, such as inflammatory bowel disease (IBD) and colorectal cancer (CRC), which makes the pharmacological modulation of H2S pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 80 publications
(137 reference statements)
4
113
1
1
Order By: Relevance
“…H 2 S is an important mediator of many biological processes (angiogenesis, cytoprotection, metabolism, inflammation) and can be pro- or anti-inflammatory depending on its concentration and the particular circumstance3536. In light of these opposite effects, a recent study reported that paediatric CD patients undergoing EEN treatment and presenting with reduced colonic inflammation had increased levels of fecal H 2 S37.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S is an important mediator of many biological processes (angiogenesis, cytoprotection, metabolism, inflammation) and can be pro- or anti-inflammatory depending on its concentration and the particular circumstance3536. In light of these opposite effects, a recent study reported that paediatric CD patients undergoing EEN treatment and presenting with reduced colonic inflammation had increased levels of fecal H 2 S37.…”
Section: Discussionmentioning
confidence: 99%
“…), found to be enriched in inflammatory bowel conditions as well as periodontal disease and metabolic syndrome[344,345], overlap significantly with those identified as pathogenic, nitratereducing Proteobacteria in the inflammatory gut and cystic fibrosis lung[323,337]. Indeed, there remains conflicting evidence regarding the precise role of H 2 S in the gut[344,347]. On one hand, it appears that lower concentrations of endogenously derived H 2 S exert beneficial cytoprotective, antioxidant and anti-inflammatory actions[344,348351], while on the other, increased H 2 S formation by SRB can promote oxidant formation, impair colonic epithelial H 2 S detoxification and induce cytotoxicity and disruption of intestinal barrier integrity, thereby driving local and systemic inflammation[344,347,352,353].…”
Section: Dysbiosis Of the Microbiome In Pulmonary Hypertension And Vascmentioning
confidence: 99%
“…Indeed, there remains conflicting evidence regarding the precise role of H 2 S in the gut[344,347]. On one hand, it appears that lower concentrations of endogenously derived H 2 S exert beneficial cytoprotective, antioxidant and anti-inflammatory actions[344,348351], while on the other, increased H 2 S formation by SRB can promote oxidant formation, impair colonic epithelial H 2 S detoxification and induce cytotoxicity and disruption of intestinal barrier integrity, thereby driving local and systemic inflammation[344,347,352,353]. Certainly, further understanding of the roles that H 2 S concentration, substrate, and location play in inflammation and nitrate metabolism remain to be more fully elucidated.…”
Section: Dysbiosis Of the Microbiome In Pulmonary Hypertension And Vascmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a gasotransmitter that regulates inflammatory and cell cycle processes(6). It is biosynthesized by three different enzymes, cystathionine γ-lyase (CSE), cystathionine ß-synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (3-MST)(7).…”
Section: Introductionmentioning
confidence: 99%